Mehrsprachige literale Förderung für die ganze Familie (Melifa) - Trix Bürki; Swantje Rehfeld; Katja Schnitzer (Babylonia)
Melifa is a school-based plurilingual literacy development programme for the whole family. It has been an integral part of the study programme for ongoing primary school teachers at the School of Education, University of Applied Sciences North-Western Switzerland (PH FHNW) since 2013 and was designed to valorize and further promote individual plurilingualism. Within Melifa, students developed concepts and material for Family Literacy Events (FLE) in places of relevance for education in general: in schools, including kindergarten, play groups, family centres and libraries, literature nights, mother-child groups of specific language groups, parent events, swimming pools and other public places. The emphasis is on reaching parents where they are and using the individual plurilingualism of the students to do this. The project is currently also conceptualizing, implementing and evaluating a program for plurilingual literacy development in cooperation with a partner primary school.